VARIETIES OF FIGS GROWN IN SURKHANDARYA REGION - A.E. Mirzaev; O'.O. Mirzaev (Bright Mind Publishing, 2025)
In this article, the origin of the fig plant, Information is provided on its distribution in Uzbekistan, biological and economic characteristics, promising varieties recommended for planting, and pollinating varieties of figs.
Keywords: Fig Varieties, Family, Class, Species, Blastophaga Insect, Pollinator, Non-Pollinator (Parthenocarp), Generation 1, Generation 2, Yield, Introduction, Disease and pests.